2019
DOI: 10.1055/s-0039-1697634
|View full text |Cite
|
Sign up to set email alerts
|

Ossified Spinal Meningioma: A Case Report and a Review of the Literature

Abstract: Ossified spinal meningiomas are a rare form of spinal tumors. These tumors increase surgical morbidities due to their hard consistency and strong adhesion to the neural tissue and relatively narrow surgical space. Here, the authors describe the clinical findings, surgical strategies, and histological findings of a patient with an ossified meningioma. Preoperative diagnosis of these tumors can prevent surgical morbidities. Total resection can be curative with the application of meticulous microsurgical techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…Ossification of spinal meningiomas is attributed to metaplasia of the arachnoid. [ 21 ] Estrogen deficiency is also suspected to intensify the calcification/ossification of meningiomas where there are necrotic fibroblasts and an elevated number of collagen fibrils. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ossification of spinal meningiomas is attributed to metaplasia of the arachnoid. [ 21 ] Estrogen deficiency is also suspected to intensify the calcification/ossification of meningiomas where there are necrotic fibroblasts and an elevated number of collagen fibrils. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…Of the 35 ossified meningiomas identified in the literature, only four occurred in males[ 21 ] [ Table 1 ]. GTRs best correlate with marked neurological improvements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several case studies of meningioma with calcification had shown clinical improvements after tumor removal with [13], [14] or without en bloc resection method. [4], [15] In this case, the tumor was successfully resected with total tumor resection, both solid (calcified) tumor and soft tumor using laminectomy method and tumor resection with a posterior approach, with a satisfactory final result in improved clinical symptoms and quality of life.…”
Section: Discussionmentioning
confidence: 99%